A shift to Online Learning in Bangladesh Universities Post pandemic effect of COVID 19: A blessing or curse? - Naheem Mahtab (International Journal of Advanced Science and Technology, 2020)
As more and more people are using the internet online learning is showing its domination in conduct both college classes and general education classes. Online teaching continues to be a relatively new concept and it requires training and time to manage for those who are not accustomed to it. Rapidly transitioning to online education in the face of a sudden crisis does have its implications in the foreseeable future. (Castaneda, 2020). Online learning is also a posh endeavour. It is essential to align real life learnings and expectations of how it can guide students sick with coronavirus measures. This is often particularly the case for universities that failed to recognise online schooling earlier than the coronavirus pandemic. Both faculties and students may additionally lack the training required for satisfactory online teaching and learning. Normally, setting up online courses involves a group of professionals including academics, instructional designers, programmers and illustrators. The group will together observe systematic layout processes.Keywords: online learning, faculty training, student training